ANTIPLASMODIAL AND ANTISALMONELLA ACTIVITIES OF PHENOLIC COMPOUND FROM ROUREA COCCINEA BENTH (CONNARACEAE) - BASILE GOUETI; WILLIAM FEUDJOU; BÉNÉDICTA KPADONOU-KPOVIESSI; BARDIEU ATCHADE; SERONDO UWIKUNDA; LÉON AHOUSSI; JOACHIM GBENOU; SALOMÉ KPOVIESSI (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry, 2024)
The leaves extract of Rourea coccinea was fractionated, following the bioguided method, to give one phenolic compound named 1-caffeoylquinic acid lactone (1-CQL) (1), isolated from this plant for the first time, and the 3-O-β-D-glucopyranoside of stigmasterol (2). The structure of these compounds was determined. The Minimum Inhibitory Concentrations (MIC) for antisalmonella activity was up to 2000 µg·mL-1 for extract and fractions, and up to 500 µg·mL-1 for compound 1. The half-inhibitory Concentration (IC50) values against Plasmodium falciparum PfDd2 was 92.56 µg·mL-1 for extract and 31.24 to 77.21 µg·mL-1 for fractions. Compound 1 exhibited on the same strain an antiplasmodial activity with an IC50 value of 8.58 µg·mL-1. These results justify the use of this plant in Beninese pharmacopeia for the treatment of several diseases such as malaria.